MANAJEMEN PENJAMINAN MUTU UNTUK MENINGKATKAN KOMPETENSI MAHASISWA DI PERGURUAN TINGGI - Hanafiah; Ratnawulan, Teti; Wardoyo, Susilo (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study examines the implementation of the Internal Quality Assurance System (SPMI) at the Republic of Indonesia Defense University (Unhan), focusing on the planning, implementation, evaluation, and follow-up actions carried out by the university to improve the quality of education. The purpose of this study is to evaluate the effectiveness of SPMI at Unhan and to identify the challenges encountered at each stage. The research method employed is a qualitative approach, using interviews, observation, and documentation as data collection techniques. The results of the study show that although Unhan has demonstrated a strong commitment to planning and implementing the SPMI, several obstacles remain, such as limited resources, lack of stakeholder involvement, and challenges in developing a competency-based curriculum and teaching. Evaluation and follow-up actions were also found to be less effective, as they tended to focus more on administrative aspects rather than academic development. Therefore, this study suggests that the university improve stakeholder engagement, enhance resource management, and optimize outcome-based evaluation and follow-up actions to sustainably improve the quality of education. Keywords: Internal Quality Assurance System (SPMI), Defense University, Education Quality.